When Halal Labels Are Absent: Trust as a Mediator Between Religiosity and Repurchase Intention in the Cosmetic Industry - Muhamad Amir Ariandi; Melda Aulia Ramadhani; Martiyanti, Dwi; Rinaldi, Muhammad (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
Abstract This study aims to analyze the influence of religiosity on repurchase intention of non-halal-certified cosmetics, with trust as a mediating variable. Data were collected from Indonesian Muslim women who actively use such cosmetic products. The study employed a quantitative method and analyzed the data using the PLS-SEM approach. The findings reveal that religiosity does not directly affect repurchase intention, but it significantly influences trust. Moreover, trust significantly affects repurchase intention and mediates the relationship between religiosity and repurchase behavior. These results emphasize that while religious values are important, trust in the producer is a crucial determinant in repeated purchase decisions. This study contributes theoretically to Islamic value-based marketing and offers practical implications for non-halal cosmetic producers to enhance consumer trust through transparency and ethical product practices.